2014
DOI: 10.5657/kfas.2014.0220
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-resistance Profiles and Virulence Genes of Vibrio parahaemolyticus Isolated from Seawater in the Wando Area

Abstract: Sixty-seven Vibrio parahaemolyticus isolates from surface seawater from the Wando area, on the southern coast of Korea, were analyzed for their susceptibility to 15 different antimicrobials and the presence of virulence genes. According to the disk diffusion susceptibility test, all of the strains studied were resistant to ampicillin and oxacillin, while decreasing percentages were resistant to vancomycin (64.2%), streptomycin (56.7%), amikacin (31.3%), kanamycin (22.3%), cephalothin (20.9%), erythromycin (10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Tetracycline and ciprofloxacin are recommended antibiotics to treat V. parahaemolyticus illnesses ( Park et al, 2018 ). Previous reports performed in South Korea showed the antibiotic susceptibility profile of V. parahaemolyticus isolates in seawater samples and found that 3.0–12.2% of isolates were resistant to tetracycline and ciprofloxacin, respectively ( Son et al, 2005 ; Kim et al, 2014 ). Other studies reported using different antibiotics against V. parahaemolyticus for detecting antibiotic susceptibility ( Han et al, 2012 ; Yang J. H. et al, 2017 ; Park et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tetracycline and ciprofloxacin are recommended antibiotics to treat V. parahaemolyticus illnesses ( Park et al, 2018 ). Previous reports performed in South Korea showed the antibiotic susceptibility profile of V. parahaemolyticus isolates in seawater samples and found that 3.0–12.2% of isolates were resistant to tetracycline and ciprofloxacin, respectively ( Son et al, 2005 ; Kim et al, 2014 ). Other studies reported using different antibiotics against V. parahaemolyticus for detecting antibiotic susceptibility ( Han et al, 2012 ; Yang J. H. et al, 2017 ; Park et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…All isolates (100%) were resistant to ampicillin and oxolinic acid, and 88.1% of all strains were resistant to three or more classes of antibiotics. However, all isolates were sensitive to sulfamethoxazole-trimethoprim, trimethoprim, gentamicin, chloramphenicol, and nalidixic acid (Kim et al 2014).…”
Section: Antibiotic Resistance Profiles Of V Parahaemolyticus Isolatmentioning
confidence: 97%
“…According to their results, 23 of 177 isolates were positive for the tdh gene, whereas all strains tested negative for the trh gene. On the other hand, many studies have shown that all V. parahaemolyticus stains isolated from seawater samples collected from the Korean coast were negative for the tdh and trh virulence genes (Lee and Park 2010;Kim et al 2014Kim et al , 2016aPark et al 2016). Yang et al (2017) reported that all 30 V. parahaemolyticus strains and mesozooplankton samples isolated from seawater were negative for the tdh and trh virulence genes.…”
Section: Virulence Genes Of V Parahaemolyticus Isolates In Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…, . (Son et al, 2005;Lee et al, 2007;Oh et al, 2008;Lee et al, 2009;Ryu et al, 2010;Yu et al, 2010;Kim et al, 2014;Kang et al, 2016;Kim et al, 2016). , , .…”
unclassified